Olimpíadas de matemática no ensino médio - Oliveira, Francisco Aristenes Lima (2020)
The present work demonstrates the main points regarding the teaching of mathematics in Brazil, seeking as fundamental understandings of the importance of the Mathematics Olympics and its positive or negative points for teaching in general in the country. Thus, this work presents the emergence of the Olympics in the world, as well as in Brazil, demonstrating its qualities and objectives in which it encourages the development and mathematical skills of high school students, however even with the efforts of teachers, inevitably the teaching processes in Brazil, it goes through several difficulties, not offering opportunities for professionals in the field to develop mathematics in a more advanced way for students in public schools, as can be seen in the plans proposed in the classroom in comparisons of the types of problems caused by the Mathematics Olympics OBMEP, comprising certain gaps in the teaching of the discipline, often due to adverse conditions, planning and lack of interest from the Government and the Ministry of Education in the country. The research problem identified for the search for answers is called the following question: what are the points positive, negative and impacts on the lives of teachers and students with the application of mathematical olympics in Brazil? Having as general objective The general objective of this work is to demonstrate all the positive or negative possibilities about the mathematics olympics to Brazilian students who are available all over the country in the teaching of mathematics. Following the specific objectives: to present the history of the mathematical olympics in Brazil and in the World; demonstrate the importance of mathematics olympics for high school; classify math teaching plans in schools; to present the types of planning as a way of developing the logical reasoning of mathematics in high school. The methodology used to carry out this work was the literature review, understood by the following descriptors: mathematics; olympics; amounts; students; classifications. The search carried out in several databases of Universities, Electronic Libraries and Books that covered the entire structure proposed by the chapters. In conclusion, it is shown that the teaching of mathematics in public schools in general requires more efforts and incentives for students to develop further in mathematics, thus preparing them for the Mathematical Olympics.